2003
DOI: 10.3349/ymj.2003.44.5.855
|View full text |Cite
|
Sign up to set email alerts
|

Morphological Study on the Acetabular Labrum

Abstract: For the diagnosis and treatment of the labral pathology, the cross sectional morphology of the labrum is needed. Fifty-four labra (male:female=44:10) from 32 adult Korean cadavers were cut in radial and perpendicular fashions to their longitudinal axis. Each labrum was divided into 8 segments, resulting 8 equally distanced points. To analyze the 432 cut surfaces, which consisted of 378 labra and 54 transverse acetabular ligaments cut surfaces, all dimensions of the cut surfaces were measured, and the attachmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 0 publications
0
17
0
1
Order By: Relevance
“…The boundary between the cartilage and labrum was not visible in CT image data, so the initial boundary was defined where the concave acetabulum transitioned into the convex acetabular rim (Figure 2). A previous investigation demonstrated that the extent of the labrum on the medial side of the acetabular rim is variable (Won et al, 2003). Therefore, a second boundary was placed approximately 2 mm medial to the baseline boundary to assess the effects of the labrum extending medial to the acetabular rim (Figure 2).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The boundary between the cartilage and labrum was not visible in CT image data, so the initial boundary was defined where the concave acetabulum transitioned into the convex acetabular rim (Figure 2). A previous investigation demonstrated that the extent of the labrum on the medial side of the acetabular rim is variable (Won et al, 2003). Therefore, a second boundary was placed approximately 2 mm medial to the baseline boundary to assess the effects of the labrum extending medial to the acetabular rim (Figure 2).…”
Section: Methodsmentioning
confidence: 99%
“…The labrum is primarily composed of circumferential Type I collagen fibers (Petersen et al, 2003). The extent of the labrum medial to the acetabular rim varies by subject and location in the acetabulum (Seldes et al, 2001; Won et al, 2003). …”
Section: Introductionmentioning
confidence: 99%
“…At the time of second-look arthroscopy, one of us (HS) determined the presence or absence of labral regrowth, reconstituted labral height [28], quality of labral regrowth, and presence of any labral scarring [14] or inflammation. One previous report [20] has shown moderate to substantial intraobserver reliability for the reporting of labral pathology during hip arthroscopy.…”
Section: Methodsmentioning
confidence: 99%
“…The femoral head cartilage was assumed to be 2 mm at its thickest point, gradually reducing to zero toward the lateral edge (Eckstein, et al 1997). The labrum was defined based on morphological studies, such that it covered the femoral head cartilage in the unloaded condition with a triangular cross-section and a height of 7 mm from the acetabular rim to the tip (Won, et al 2003). In order to create a wide range of hip geometries, a consecutive series of α and CE angles were chosen for evaluation, covering normal and pathological joint morphologies.…”
Section: Hip Modelsmentioning
confidence: 99%